Ministry of Finance Decree No. 533 of the Year 2023 On the Rules of Enforcing the Provisions of law No. 172 of the year 2023 On Determining an Exceptional Cost-of-living Allowance for the Workers Addressed by the Provisions of the Civil Service Law, the State Civil Servants Non-Addressed Thereby, and on Determining an Increase of the Exceptional Grant for the Workers of the Public Sector Companies and Public Business Sector Companies Prescribed by Law No. 166 of the Year 2022, Giving an Exceptional Grant To Pensioners or Their Beneficiaries, And Amending Certain Provisions of the Social Insurance and Pensions law promulgated by law no. 148 of the year 2019 = وزارة المالية قرار رقم 533 لسنة 2023 بشأن قواعد تنفيذ أحكام القانون رقم 172 لسنة 2023 بتقرير زيادة في علاوة غلاء المعيشة الاستثنائية للموظفين المخاطبين بقانون الخدمة المدنية والعاملين بالدولة غير المخاطبين به وبتقرير زيادة المنحة الاستثنائية للعاملين بشركات القطاع العام وقطاع الأعمال العام المقررة بموجب القانون رقم 166 لسنة 2022 ومنح أصحاب المعاشات أو المستحقين عنهم منحة استثنائية وبتعديل بعض أحكام قانون التأمينات الاجتماعية والمعاشات الصادر بالقانون رقم 148 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic